On the structural and bandgap properties of mist-CVD-grown κ-Ga2O3 post continuous temperature annealing - Yara Banda; Yanqing Jia; Seong-Ho Cho; Bambar Davaasuren; Mohamed Ben Hassine; Qingxiao Wang; Dalaver H. Anjum; Qiaoqiang Gan; Zhenqiang Ma; Si-Young Bae; Tien Khee Ng; Boon S. Ooi (AIP Advances)
We investigate the continuous annealing of orthorhombic κ-Ga2O3 films on AlN/c-plane sapphire templates grown by Mist Chemical Vapor Deposition (mist-CVD) using in situ high-temperature x-ray diffraction (HT-XRD). Increasing the annealing temperature from 400 to 1100 °C in both vacuum and ambient air reveals a phase transition onset at 825 °C. High-resolution transmission electron microscopy and XRD demonstrated that annealing within the stability window of 650 to 775 °C effectively improves the crystal quality of the κ-Ga2O3 thin film. Optical transmittance and low-loss electron energy loss spectroscopy (EELS) show the pristine film’s bandgaps to be 4.96 and 4.67 eV, respectively, with reduced bandgaps in annealed films due to increased defect density. EELS-derived optical joint density of states indicates that air-annealing fosters sub-bandgap radiative processes, while vacuum annealing suppresses them, qualitatively correlated with the observed photoluminescence intensity variations. The results of this comprehensive high-temperature annealing study offer crucial insight into the influence of annealing ambient conditions on the crystallographic properties of κ-Ga2O3 films and the associated evolution of extended sub-bandgap states.